Protein recommendations for weight loss in elite athletes: A focus on body composition and performance - Hector, A. J.; Phillips, S. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
There exists a large body of scientific evidence to support protein intakes in excess of the recommended dietary allowance (RDA) (0.8g protein/kg/d) to promote the retention of skeletal muscle and loss of adipose tissue during dietary energy restriction. Diet-induced weight loss with as low as possible ratio of skeletal muscle to fat mass loss is a situation we refer to as high quality weight loss. We propose that high quality weight loss is often of importance to elite athletes in order to maintain their muscle (engine) and shed unwanted fat mass, potentially improving athletic performance. Current recommendations for protein intakes during weight loss in athletes are set at 1.6-2.4g protein/kg/d. However, the severity of the caloric deficit and type and intensity of training performed by the athlete will influence at what end of this range athletes choose to be at. Other considerations regarding protein intake that may help elite athletes achieve weight loss goals include the quality of protein consumed, and the timing and distribution of protein intake throughout the day. This review highlights the scientific evidence used to support protein recommendations for high quality weight loss and preservation of performance in athletes. Additionally, the current knowledge surrounding the use of protein supplements, branched chain amino acids (BCAA), ß-Hydroxy ß-Methylbutyrate (HMB), and other dietary supplements with weight loss claims will be discussed.